Analysis of a trial assessing the long‐term effectiveness of salicylic acid plasters compared with scalpel debridement in facilitating corn resolution in patients with multiple corns. Issue 6 (15th December 2015) - Stephenson, John; Farndon, Lisa; Concannon, Michael
Abstract: This study assesses the effect of salicylic acid plasters on the time to resolution of 324 corns experienced by 201 participants taking part in a randomized controlled trial. While the rate of corn resolution was substantively higher in the treatment group than in the control group, treatment was found to be not significantly related to time to corn recurrence when analyzed over the full 12‐month follow‐up period. Parametric survival analysis modeling of interval‐censored data and incorporating patient‐specific frailty terms was utilized, to model correlation of corns within patients (hazard ratio [HR], 1.189; 95% confidence interval [CI], 0.780–1.813; P = 0.422). Median resolution times were 10.0 months for corns in the treatment group and 13.4 months for corns in the control group. Controlling for treatment, corn type was found to be related to resolution time, with dorsal/interdigital (ID) corns showing better resolution than plantar corns (HR, 1.670; 95% CI, 1.061–2.630; P = 0.027). Median resolution times were 5.9 months for dorsal/ID corns and 14.9 months for plantar corns. Secondary measures relating to quality of life (QoL) and foot‐related disability, using the EQ‐5D questionnaire and the Manchester Foot Pain and Disability Index (MFPDI), were also assessed at the patient level in multivariate models. Treatment was not significantly related to any of these measures over the whole period of analysis. However, a trend analysis revealed a quadratic trend in QoL and MFPDI scores, arising from a substantive initial improvement between baseline and 3 months, followed by a gradual decrease between 3 and 12 months.